Improving Student’s Reading Comprehension in Recount Text by Using Concept Oriented Reading Instruction - Imam nur Aziz; Nur Hamidhah (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research aims to improve the student’s reading comprehension in recount text by using Concept Oriented Reading Instruction strategy. The subject of this research was 8th Grade of Mambaul Muflihin Islamic Junior High School. The research was classroom action research (CAR). It is divided into pre-cycle, cycle I and cycle II. The writer used test, observation, and interview as the instrument of collecting data. Based on the results of test showed that there was an improvement of students achievement in reading recount text. The mean of pre-test was 47, 82 then, the mean of the first cycle was 56,95 and in the cycle II was 82,60. It indicated that the scores in each cycle was increased and the mean score of post-test in cycle II were better than the mean of the post-test of cycle I. Based on observation and interview showed that most of the students had improvement motivation in learning reading. Moreover, CORI strategy can improve the learning motivation and achievement especially in comprehending recount text. The finding shows an improvement in student’s reading comprehension through Concept Oriented Reading Instruction (CORI) strategy. Thus, it can be concluded that the Concept Oriented Reading Instruction can improve the reading comprehension in recount text